A boron-doped high-capacity solid-state battery anode material and a method of making the same

CN122907613APending Publication Date: 2026-10-13ANHUI NANDU HUATUO NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611044751.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-14
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0002]全固态锂电池凭借高能量密度、高安全性能等优势,成为新能源储能与动力电池领域的重点发展方向,硅基负极因理论储锂容量高,是提升全固态电池能量密度的理想候选材料,但传统的硅基负极仍存在诸多亟待完善的技术短板,单质硅本身电子导电性能偏弱,充放电过程中易产生巨大体积膨胀,引发颗粒粉化、电极结构坍塌脱落,同时硅基材料表面界面缺陷多,与固态电解质间固-固界面接触阻抗大,易发生不可逆副反应,造成首次库仑效率偏低

Benefits of technology

[0021]1、本发明的镍钴有机金属骨架具有三维多孔骨架结构与丰富配位活性位点,元素组成中钴、镍金属位点与有机配体协同构筑多级孔道,固态复合电解质依托含氟高分子、吡咯烷离子液体与磺酰亚胺锂盐的多元元素配伍,同时镶嵌镍钴有机金属骨架形成有机-无机复合导电网络,高分子导锂复合物以硼掺杂硅为基体,硼元素掺杂改性硅晶格并结合聚醚高分子与锂盐配位包覆,构建连续锂离子传输界面层,三者在元素组分互补、微观结构互嵌下产生显著协同作用,一方面硼原子掺杂优化硅基体电子导电晶格、多孔MOF孔道与高分子包覆层缩短锂离子迁移路径,另一方面固态复合电解质与高分子导锂复合物界面相容性优异,大幅降低离子传输阻力与极化损耗,充分激活硅基材料储锂活性位点,使负极材料能够发挥更高的储锂容量,显著提升负极材料的首次放电比容量,实现高容量储能特性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a boron-doped high-capacity solid-state battery negative material and a preparation method thereof, belongs to the technical field of full solid-state lithium battery negative materials, and mainly aims at the technical problem of how to further improve the energy storage performance and cycle endurance performance of the boron-doped high-capacity solid-state battery negative material, and specifically comprises the following components in parts by weight: 3-5 parts of conductive carbon black, 4-6 parts of butadiene styrene rubber, 18-22 parts of a solid-state composite electrolyte, 100 parts of a high-molecular lithium-conducting compound and 200-220 parts of deionized water. The application further improves the energy storage performance and cycle endurance performance of the prepared boron-doped high-capacity solid-state battery negative material through the synergistic effect between the prepared solid-state composite electrolyte and the high-molecular lithium-conducting compound.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of all-solid-state lithium battery anode material technology, specifically to a boron-doped high-capacity solid-state battery anode material and its preparation method. Background Technology

[0002] All-solid-state lithium batteries have become a key development direction in the fields of new energy storage and power batteries due to their advantages such as high energy density and high safety performance. Silicon-based anodes are ideal candidate materials for improving the energy density of all-solid-state batteries because of their high theoretical lithium storage capacity. However, traditional silicon-based anodes still have many technical shortcomings that need to be improved. Elemental silicon itself has weak electronic conductivity and is prone to huge volume expansion during charging and discharging, which can lead to particle pulverization and electrode structure collapse and detachment. At the same time, silicon-based materials have many surface interface defects and high solid-solid interface contact resistance with solid electrolytes, which can easily cause irreversible side reactions, resulting in low initial coulombic efficiency.

[0003] Currently, conventional silicon-based anodes rely solely on simple carbon coating or single-element doping modification. This limited modification approach makes it difficult to achieve synergistic optimization across multiple dimensions, including lattice conductivity, interfacial lithium conduction, and structural buffering. Ordinary liquid electrolytes are unsuitable for all-solid-state battery systems, exhibiting poor interfacial compatibility and discontinuous ion transport pathways, further restricting anode rate performance and lithium storage capacity. Furthermore, the lack of a functionalized inorganic framework and polymer composite electrolyte matching design makes it impossible to effectively anchor lithium salt and ionic liquid components. The polymer matrix is ​​prone to crystallization, limiting ion conduction efficiency and resulting in rapid capacity decay under long-cycle conditions. Cycle durability performance is insufficient to meet practical application requirements. In addition, traditional silicon-based anodes lack an ordered surface lithium-conducting coating structure, making it impossible to construct a continuous flexible ion transport interface on the silicon particle surface. This hinders adaptation to silicon volume deformation and prevents effective reduction of interparticle interfacial impedance.

[0004] To address this technical deficiency, a solution is proposed. Summary of the Invention

[0005] The purpose of this invention is to provide a boron-doped high-capacity solid-state battery anode material and its preparation method, mainly addressing the technical problem of how to further improve the energy storage performance and cycle durability of the boron-doped high-capacity solid-state battery anode material.

[0006] The objective of this invention can be achieved through the following technical solution: a boron-doped high-capacity solid-state battery anode material, comprising the following components by weight: 3-5 parts conductive carbon black, 4-6 parts styrene-butadiene rubber, 18-22 parts solid composite electrolyte, 100 parts polymer lithium-conducting composite and 200-220 parts deionized water.

[0007] The solid composite electrolyte is prepared by solvent coordination composite of a fluorine-containing polymer matrix, a pyrrolidine ionic liquid and a lithium sulfonylimide salt, and then embedded on a metal-organic framework.

[0008] The polymeric lithium-conducting composite is prepared by modifying a silicon matrix with high-temperature boron doping, followed by coating with a polyether polymer and a lithium salt through coordination complexation.

[0009] Furthermore, the preparation method of the solid composite electrolyte is as follows: polyvinylidene fluoride-hexafluoropropylene, 1-n-butyl-1-methylpyrrolidone bis(trifluoromethanesulfonyl)imide and lithium bis(trifluoromethanesulfonyl)imide are added to a reaction vessel containing N-methylpyrrolidone, stirred at 40-50℃ for 10-12h, a nickel-cobalt organometallic framework is added, and stirring is continued for 6-8h. The mixture is then transferred to a polytetrafluoroethylene mold and dried in a vacuum drying oven at 70℃ for 24h to obtain the solid composite electrolyte.

[0010] Furthermore, the ratio of polyvinylidene fluoride-hexafluoropropylene, 1-n-butyl-1-methylpyrrolidine bis(trifluoromethanesulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, N-methylpyrrolidone and nickel cobalt organometallic framework is 10g:2-2.8g:6-7g:50-60mL:12-16g.

[0011] Furthermore, the preparation method of the nickel-cobalt organometallic framework is as follows: Tristyric acid is added to a reaction vessel containing anhydrous ethanol and stirred for 20-30 min. Then, cobalt nitrate hexahydrate and nickel chloride hexahydrate are added to the mixture, and stirring is continued for 10-20 min. The mixture is then transferred to a high-pressure reaction vessel and reacted at 140-150℃ for 12-15 h. After the reaction is completed, the mixture is centrifuged, and the product is washed 3-4 times with anhydrous ethanol. The product is then placed in a vacuum drying oven and dried at 60℃ for 12 h to obtain the nickel-cobalt organometallic framework.

[0012] Furthermore, the ratio of the amount of pyromellitic acid, anhydrous ethanol, cobalt nitrate hexahydrate and nickel chloride hexahydrate used is 0.6g:70-80mL:0.6g:0.24-0.26g.

[0013] Furthermore, the polymeric lithium-conducting composite is prepared by the following steps:

[0014] A1. Under an argon atmosphere, silicon powder, boric acid and boron trioxide are mixed and ball-milled at a speed of 200-400 r / min for 40-60 min. The mixture is then transferred to a tube furnace and heated to 900-1100℃ at a heating rate of 3-5℃ / min. After holding at this temperature for 6-8 h, the mixture is cooled to room temperature with the furnace to obtain boron-doped silicon material.

[0015] A2. Under an argon atmosphere, boron-doped silicon material is added to a reactor containing toluene and ultrasonically dispersed for 20-30 minutes. Then, polyethylene oxide and lithium tetrafluoroborate are added, the temperature is raised to 50-60℃, and the mixture is stirred at 300-500 r / min for 4-5 hours. After stirring, the mixture is transferred to a vacuum drying oven and dried at 80-90℃ for 8-10 hours. The mixture is then passed through a 200-mesh sieve to obtain a polymer lithium-conducting composite.

[0016] Furthermore, in step A1, the ratio of silicon powder, boric acid, and boron trioxide is 100g:3-4g:1-2g; in step A2, the ratio of boron-doped silicon material, toluene, and lithium tetrafluoroborate is 100g:400-500mL:8-10g:3-5g.

[0017] This invention also proposes a method for preparing boron-doped high-capacity solid-state battery anode material:

[0018] S1. Add the polymer lithium-conducting composite, solid composite electrolyte and conductive carbon black to a mixer and premix for 5-10 min. Then add the styrene-butadiene rubber aqueous solution and stir at 20-30℃ for 20-30 min to obtain the aqueous negative electrode slurry.

[0019] S2. The aqueous negative electrode slurry is uniformly coated on the surface of copper foil with a coating thickness of 20-30μm. After pre-drying at room temperature for 40-60min, it is transferred to a vacuum drying oven and dried at 60℃ for 2h, and then heated to 80℃ for 6-8h. After drying, the electrode sheet is rolled at 100-120N / mm to obtain boron-doped high-capacity solid-state battery negative electrode material.

[0020] The present invention has the following beneficial effects:

[0021] 1. The nickel-cobalt organometallic framework of this invention has a three-dimensional porous framework structure and abundant coordination active sites. In the elemental composition, cobalt and nickel metal sites and organic ligands synergistically construct multi-level channels. The solid composite electrolyte relies on the multi-element combination of fluorine-containing polymer, pyrrolidine ionic liquid and sulfonylimide lithium salt, and simultaneously embeds the nickel-cobalt organometallic framework to form an organic-inorganic composite conductive network. The polymer lithium-conducting composite uses boron-doped silicon as the matrix. Boron element doping modifies the silicon lattice and combines it with polyether polymer and lithium salt coordination coating to construct a continuous lithium-ion transport interface layer. The three elements produce a significant synergistic effect under the complementary elemental composition and interlocking microstructure. On the one hand, boron atom doping optimizes the electronic conductive lattice of the silicon matrix, the porous MOF channels and the polymer coating layer to shorten the lithium-ion migration path. On the other hand, the solid composite electrolyte and the polymer lithium-conducting composite have excellent interfacial compatibility, which greatly reduces ion transport resistance and polarization loss, fully activates the lithium storage active sites of silicon-based materials, enables the anode material to exert a higher lithium storage capacity, significantly improves the first discharge specific capacity of the anode material, and achieves high-capacity energy storage characteristics.

[0022] 2. In this invention, the three-dimensional porous confined structure of the nickel-cobalt organometallic framework can anchor the ionic liquid and lithium salt components, suppress crystallization defects in the polymer matrix, and reduce the occurrence of interfacial side reactions during charging and discharging. The solid composite electrolyte forms a stable ion conduction network through multi-element coordination, which can be uniformly spread in the gaps between negative electrode particles, optimize the solid-solid interface contact state, and reduce the interfacial impedance. The polymer lithium-conducting composite adapts to the silicon-based charge-discharge volume expansion through a polyether polymer flexible coating layer. Boron doping can suppress lattice collapse and particle pulverization and shedding. The three rely on the synergistic adaptation of elemental composition matching and special microstructure to reduce the irreversible consumption of lithium ions during the first charge-discharge process, effectively improve the first coulombic efficiency, maintain the integrity of the overall electrode structure and maintain a continuous and stable electronic and ion conduction pathway during long-term charge-discharge cycles, alleviate the structural decay and capacity decay of active materials, significantly improve the cycle discharge capacity retention rate of negative electrode materials, and greatly enhance the cycle durability stability of boron-doped high-capacity solid-state battery negative electrode materials. Detailed Implementation

[0023] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0024] In this application, the conductive carbon black is selected from Lingshou County Laipeng Mineral Products Business Department, CAS No. 1333-86-4, and the mesh size is 325.

[0025] In this application, the copper foil is selected from Suzhou Qiandingli Electronic Technology Co., Ltd., with a specification of 4.5μm and a grade of T2;

[0026] In this application, polyvinylidene fluoride-hexafluoropropylene is selected from Hubei Maidehao Biotechnology Co., Ltd., with CAS number 9011-17-0 and model number MDH;

[0027] In this application, the silicon powder is selected from Jinan Chuanze New Materials Co., Ltd., CAS No. 200274779, and has a mesh size of 325.

[0028] In this application, the polyethylene oxide is selected from Wuhan Camick Technology Co., Ltd., CAS No. 68441-17-8, with a molecular weight of 100,000;

[0029] In this application, the lithium-ion battery electrolyte is selected from Shandong Xuchen Chemical Technology Co., Ltd., CAS No. 21324-40-3.

[0030] Example 1

[0031] This embodiment provides a method for preparing a boron-doped high-capacity solid-state battery anode material, including the following steps:

[0032] S1. Preparation of nickel-cobalt organometallic framework

[0033] Weigh 12g of trimesic acid and add it to a reaction vessel containing 1400mL of anhydrous ethanol. Stir for 20min. Then add 12g of cobalt nitrate hexahydrate and 4.8g of nickel chloride hexahydrate. Continue stirring for 10min. Transfer to a high-pressure reaction vessel and react at 140℃ for 12h. After the reaction is complete, centrifuge and wash the product three times with anhydrous ethanol. Place it in a vacuum drying oven and dry at 60℃ for 12h to obtain a nickel-cobalt organometallic framework.

[0034] Reaction mechanism for the preparation of nickel-cobalt organometallic frameworks:

[0035] In anhydrous ethanol, pyromellitic acid is fully dissolved and dispersed, exposing carboxyl coordination active sites. After cobalt nitrate hexahydrate and nickel chloride hexahydrate dissociate, cobalt ions and nickel ions are released and mixed with organic ligands at the molecular level. Under solvothermal conditions, pyromellitic acid acts as a bridging ligand and forms carboxyl coordination bonds with cobalt and nickel ions. Through coordination self-assembly under high temperature and pressure, intermolecular hydrogen bonding and π-π stacking of aromatic rings, a three-dimensional porous nickel-cobalt organometallic framework is constructed in situ with bimetallic ions as structural nodes and pyromellitic acid as an organic linker. After separation, impurity removal and drying, a nickel-cobalt bimetallic organometallic framework material with high crystallinity, well-developed pore structure and uniform morphology is finally obtained.

[0036] S2. Preparation of solid composite electrolytes

[0037] Weigh out 10g of polyvinylidene fluoride-hexafluoropropylene, 2g of 1-n-butyl-1-methylpyrrolidone bis(trifluoromethanesulfonyl)imide and 6g of lithium bis(trifluoromethanesulfonyl)imide and add them to a reactor containing 50mL of N-methylpyrrolidone. After stirring at 40℃ for 10h, add 12g of nickel cobalt organometallic framework and continue stirring for 6h. Then transfer the mixture to a polytetrafluoroethylene mold and dry it in a vacuum drying oven at 70℃ for 24h to obtain a solid composite electrolyte.

[0038] Reaction mechanism for preparing solid composite electrolytes:

[0039] N-methylpyrrolidone, as a highly polar solvent, fully dissolves polyvinylidene fluoride-hexafluoropropylene under stirring conditions. Simultaneously, 1-n-butyl-1-methylpyrrolidone bis(trifluoromethanesulfonyl)imide ionic liquid and lithium bis(trifluoromethanesulfonyl)imide are completely dissolved and dissociated to release lithium ions. The ionic liquid plasticizes and inhibits crystallization of the polymer matrix, expands the amorphous region, and synergistically constructs a continuous lithium-ion conduction pathway with the lithium salt. Then, a nickel-cobalt organometallic framework is added and thoroughly stirred to achieve uniform dispersion. The porous structure and surface effect of the nickel-cobalt organometallic framework further inhibit polymer crystallization, constructs rapid lithium transport channels, and enhances the mechanical stability of the film. Finally, the film is cast and dried using a polytetrafluoroethylene mold to remove the solvent and solidify the matrix. The ionic liquid, lithium salt, and nickel-cobalt organometallic framework are stably embedded in the polymer network, ultimately forming a solid composite electrolyte with low crystallinity, high ionic conductivity, excellent mechanical properties, and stable structure.

[0040] S3. Preparation of polymeric lithium-conducting composites

[0041] Under an argon atmosphere, 100g of silicon powder, 3g of boric acid and 1g of boron trioxide were weighed and mixed. After ball milling at 200r / min for 40min, the mixture was transferred to a tube furnace and heated to 900℃ at a heating rate of 3℃ / min. After holding at that temperature for 6h, the mixture was cooled to room temperature with the furnace to obtain boron-doped silicon material.

[0042] Under an argon atmosphere, 100g of boron-doped silicon material was weighed and added to a reactor containing 400mL of toluene. The mixture was ultrasonically dispersed for 20min. Then, 8g of polyethylene oxide and 3g of lithium tetrafluoroborate were added. The mixture was heated to 50℃ and stirred at 300r / min for 4h. The mixture was then transferred to a vacuum drying oven and dried at 80℃ for 8h. After passing through a 200-mesh sieve, a polymer lithium-conducting composite was obtained.

[0043] Reaction mechanism for preparing polymeric lithium-conducting complexes:

[0044] The polyethylene oxide (PEO) molecular chains are fully extended and activated, and Lewis acid-base interactions occur between the etheroxy groups on the PEO molecular chains and the lithium ions dissociated from lithium tetrafluoroborate. Specifically, the lithium ions coordinate with the lone pairs of electrons on the etheroxy groups, thereby forming a polymeric electrolyte network that can dissociate lithium salts and provide ion migration channels. In this system, toluene acts as a good solvent to fully dissolve the polymer chains and lithium salts and reduce the viscosity of the system. Combined with the cavitation effect of ultrasound and the shear force of mechanical stirring, the dissolved polymer chains and lithium ions are forced to be uniformly adsorbed and coated on the surface and pores of boron-doped silicon particles. Subsequent vacuum drying removes the solvent, induces conformational rearrangement and contraction of the polymer chains, and finally solidifies in situ on the surface of the silicon particles to form a dense, continuous, and flexible polymeric composite coating layer with excellent ion conductivity.

[0045] S4. Preparation of boron-doped high-capacity solid-state battery anode materials

[0046] Weigh out 100 parts by weight of high molecular weight lithium-conducting composite, 18 parts by weight of solid composite electrolyte and 3 parts by weight of conductive carbon black and add them to a mixer for premixing for 5 minutes. Then add 204 parts by weight of styrene-butadiene rubber aqueous solution and stir at 20°C for 20 minutes to obtain aqueous negative electrode slurry.

[0047] Aqueous negative electrode slurry was uniformly coated on the surface of copper foil with a coating thickness of 20 μm. After pre-drying at room temperature for 40 min, it was transferred to a vacuum drying oven and dried at 60 °C for 2 h, then heated to 80 °C for 6 h. After drying, the electrode sheet was rolled at 100 N / mm to obtain boron-doped high-capacity solid-state battery negative electrode material.

[0048] Example 2

[0049] This embodiment provides a method for preparing a boron-doped high-capacity solid-state battery anode material, including the following steps:

[0050] S1. Preparation of nickel-cobalt organometallic framework

[0051] Weigh 12g of trimesic acid and add it to a reaction vessel containing 1500mL of anhydrous ethanol. Stir for 25min. Then add 12g of cobalt nitrate hexahydrate and 5.0g of nickel chloride hexahydrate. Continue stirring for 15min. Transfer to a high-pressure reaction vessel and react at 145℃ for 13.5h. After the reaction is complete, centrifuge and wash the product three times with anhydrous ethanol. Place it in a vacuum drying oven and dry at 60℃ for 12h to obtain a nickel-cobalt organometallic framework.

[0052] S2. Preparation of solid composite electrolytes

[0053] Weigh out 10g of polyvinylidene fluoride-hexafluoropropylene, 2.4g of 1-n-butyl-1-methylpyrrolidone bis(trifluoromethanesulfonyl)imide and 6.5g of lithium bis(trifluoromethanesulfonyl)imide and add them to a reactor containing 55mL of N-methylpyrrolidone. After stirring at 45℃ for 11h, add 14g of nickel cobalt organometallic framework and continue stirring for 7h. Then transfer the mixture to a polytetrafluoroethylene mold and dry it in a vacuum drying oven at 70℃ for 24h to obtain a solid composite electrolyte.

[0054] S3. Preparation of polymeric lithium-conducting composites

[0055] Under an argon atmosphere, 100g of silicon powder, 3.5g of boric acid and 1.5g of boron trioxide were weighed and mixed. After ball milling at 300r / min for 50min, the mixture was transferred to a tube furnace and heated to 1000℃ at a heating rate of 4℃ / min. After holding at this temperature for 7h, the mixture was cooled to room temperature with the furnace to obtain boron-doped silicon material.

[0056] Under an argon atmosphere, 100g of boron-doped silicon material was weighed and added to a reactor containing 450mL of toluene. The mixture was ultrasonically dispersed for 25min. Then, 9g of polyethylene oxide and 4g of lithium tetrafluoroborate were added. The mixture was heated to 55℃ and stirred at 400r / min for 4.5h. The mixture was then transferred to a vacuum drying oven and dried at 85℃ for 9h. After passing through a 200-mesh sieve, a polymer lithium-conducting composite was obtained.

[0057] S4. Preparation of boron-doped high-capacity solid-state battery anode materials

[0058] Weigh out 100 parts by weight of high molecular weight lithium-conducting composite, 20 parts by weight of solid composite electrolyte and 4 parts by weight of conductive carbon black and add them to a mixer for premixing for 7 minutes. Then add 215 parts by weight of styrene-butadiene rubber aqueous solution and stir at 25°C for 25 minutes to obtain aqueous negative electrode slurry.

[0059] Aqueous negative electrode slurry was uniformly coated on the surface of copper foil with a coating thickness of 25 μm. After pre-drying at room temperature for 50 min, it was transferred to a vacuum drying oven and dried at 60 °C for 2 h, then heated to 80 °C for 7 h. After drying, the electrode sheet was rolled at 110 N / mm to obtain boron-doped high-capacity solid-state battery negative electrode material.

[0060] Example 3

[0061] This embodiment provides a method for preparing a boron-doped high-capacity solid-state battery anode material, including the following steps:

[0062] S1. Preparation of nickel-cobalt organometallic framework

[0063] Weigh 12g of trimesic acid and add it to a reaction vessel containing 1600mL of anhydrous ethanol. Stir for 30min. Then add 12g of cobalt nitrate hexahydrate and 5.2g of nickel chloride hexahydrate. Continue stirring for 20min. Transfer to a high-pressure reaction vessel and react at 150℃ for 15h. After the reaction is complete, centrifuge and wash the product 4 times with anhydrous ethanol. Place it in a vacuum drying oven and dry at 60℃ for 12h to obtain a nickel-cobalt organometallic framework.

[0064] S2. Preparation of solid composite electrolytes

[0065] Weigh out 10g of polyvinylidene fluoride-hexafluoropropylene, 2.8g of 1-n-butyl-1-methylpyrrolidone bis(trifluoromethanesulfonyl)imide and 7g of lithium bis(trifluoromethanesulfonyl)imide and add them to a reactor containing 60mL of N-methylpyrrolidone. After stirring at 50℃ for 12h, add 16g of nickel cobalt organometallic framework and continue stirring for 8h. Then transfer the mixture to a polytetrafluoroethylene mold and dry it in a vacuum drying oven at 70℃ for 24h to obtain a solid composite electrolyte.

[0066] S3. Preparation of polymeric lithium-conducting composites

[0067] Under an argon atmosphere, 100g of silicon powder, 4g of boric acid and 2g of boron trioxide were weighed and mixed. After ball milling at 400r / min for 60min, the mixture was transferred to a tube furnace and heated to 1100℃ at a heating rate of 5℃ / min. After holding at this temperature for 8h, the mixture was cooled to room temperature with the furnace to obtain boron-doped silicon material.

[0068] Under an argon atmosphere, 100g of boron-doped silicon material was weighed and added to a reactor containing 500mL of toluene. The mixture was ultrasonically dispersed for 30min. Then, 10g of polyethylene oxide and 5g of lithium tetrafluoroborate were added. The mixture was heated to 60℃ and stirred at 500r / min for 5h. The mixture was then transferred to a vacuum drying oven and dried at 90℃ for 10h. The resulting product was passed through a 200-mesh sieve to obtain a polymer lithium-conducting composite.

[0069] S4. Preparation of boron-doped high-capacity solid-state battery anode materials

[0070] Weigh out 100 parts by weight of high molecular weight lithium-conducting composite, 22 parts by weight of solid composite electrolyte and 5 parts by weight of conductive carbon black and add them to a mixer for premixing for 10 min. Then add 226 parts by weight of styrene-butadiene rubber aqueous solution and stir at 30°C for 30 min to obtain aqueous negative electrode slurry.

[0071] Aqueous negative electrode slurry was uniformly coated on the surface of copper foil with a coating thickness of 30 μm. After pre-drying at room temperature for 60 min, it was transferred to a vacuum drying oven and dried at 60 °C for 2 h, then heated to 80 °C for 8 h. After drying, the electrode sheet was rolled at 120 N / mm to obtain boron-doped high-capacity solid-state battery negative electrode material.

[0072] Comparative Example 1

[0073] The difference between this comparative example and Example 3 is that steps S1 and S2 are omitted, and the solid composite electrolyte in step S4 is replaced with a commercially available lithium-ion battery electrolyte.

[0074] Comparative Example 2

[0075] The difference between this comparative example and Example 3 is that the preparation of the polymer lithium-conducting composite in step S3 is omitted, and the boron-doped silicon material prepared in step S3 is used to replace the polymer lithium-conducting composite in step S4.

[0076] Performance testing:

[0077] The initial discharge specific capacity and initial coulombic efficiency of the boron-doped high-capacity solid-state battery anode materials prepared in Examples 1-3 and Comparative Examples 1-2 were determined in accordance with the standard GB / T 24533-2019 "Graphite Anode Materials for Lithium-ion Batteries".

[0078] The cycle discharge capacity retention of the boron-doped high-capacity solid-state battery anode materials prepared in Examples 1-3 and Comparative Examples 1-2 was determined according to standard GB / T 44027.1-2024 "Determination Methods for Carbon Materials - Part 1: Determination of Initial Discharge Specific Capacity, Initial Coulombic Efficiency, and Capacity Retention Rate at Different Discharge Rates". The specific test results are shown in Table 1 below:

[0079] Table 1 - Performance Test Data of Samples

[0080]

[0081] Data Analysis:

[0082] Comparative analysis of the data in Table 1 above shows that the boron-doped high-capacity solid-state battery anode material prepared by this invention has a first discharge specific capacity of 1425 mAh / g, a first coulombic efficiency of 92.7%, and a cycle discharge capacity retention rate of 87.1%.

[0083] Comparative Example 1 eliminated the nickel-cobalt organometallic framework and solid-state composite electrolyte preparation, directly using commercially available lithium-ion battery electrolytes as substitutes. Due to the lack of the three-dimensional porous channel structure of the nickel-cobalt organometallic framework, the plasticizing and crystal-inhibiting effect of ionic liquids, and the synergistic lithium conduction effect of multiple lithium salts, it was impossible to construct a continuous and stable organic-inorganic composite ion transport network. The solid-solid interface impedance increased significantly, resulting in high lithium-ion migration resistance and difficulty in fully activating lithium storage active sites. This led to a decrease in the initial discharge specific capacity to 1029 mAh / g. At the same time, due to the lack of MOF framework anchoring effect, the interfacial side reactions increased, irreversible lithium-ion loss increased, and the initial coulombic efficiency decreased to 82.2%. Furthermore, the ion channels were prone to decay during cycling, and the cycle discharge capacity retention rate decreased to 73.4%.

[0084] Comparative Example 2 did not prepare a polymer lithium-conducting composite and directly used uncoated boron-doped silicon material as the negative electrode active component. Due to the lack of a flexible lithium-conducting coating layer formed by the coordination of polyether polymer and lithium salt, it could not buffer the volume expansion of silicon-based materials during charging and discharging, nor could it construct a continuous lithium-ion conduction interface on the surface of silicon particles. Boron-doped silicon particles were prone to lattice collapse, pulverization and shedding, resulting in poor electrode structure stability. This caused its initial discharge specific capacity to decrease to 1186 mAh / g and its initial coulombic efficiency to decrease to 86.4%. During long-term cycling, the active material structure continued to deteriorate, the capacity decay accelerated, and the cycle discharge capacity retention rate was only 77.8%.

[0085] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to specific implementations. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A boron-doped high-capacity solid-state battery anode material, characterized in that, It comprises the following components by weight: 3-5 parts conductive carbon black, 4-6 parts styrene-butadiene rubber, 18-22 parts solid composite electrolyte, 100 parts polymer lithium-conducting composite and 200-220 parts deionized water; The solid composite electrolyte is prepared by solvent coordination composite of a fluorine-containing polymer matrix, a pyrrolidine ionic liquid and a lithium sulfonylimide salt, and then embedded on a metal-organic framework. The polymeric lithium-conducting composite is prepared by modifying a silicon matrix with high-temperature boron doping, followed by coating with a polyether polymer and a lithium salt through coordination complexation.

2. The boron-doped high-capacity solid-state battery anode material according to claim 1, characterized in that, The solid composite electrolyte is prepared as follows: polyvinylidene fluoride-hexafluoropropylene, 1-n-butyl-1-methylpyrrolidone bis(trifluoromethanesulfonyl)imide and lithium bis(trifluoromethanesulfonyl)imide are added to a reaction vessel containing N-methylpyrrolidone. After stirring at 40-50℃ for 10-12h, a nickel-cobalt organometallic framework is added. After stirring for another 6-8h, the mixture is transferred to a polytetrafluoroethylene mold and dried in a vacuum drying oven at 70℃ for 24h to obtain the solid composite electrolyte.

3. The boron-doped high-capacity solid-state battery anode material according to claim 2, characterized in that, The ratio of polyvinylidene fluoride-hexafluoropropylene, 1-n-butyl-1-methylpyrrolidine di(trifluoromethanesulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, N-methylpyrrolidone and nickel cobalt organometallic framework is 10g:2-2.8g:6-7g:50-60mL:12-16g.

4. The boron-doped high-capacity solid-state battery anode material according to claim 2, characterized in that, The preparation method of the nickel-cobalt organometallic framework is as follows: Tristyric acid is added to a reaction vessel containing anhydrous ethanol and stirred for 20-30 min. Then, cobalt nitrate hexahydrate and nickel chloride hexahydrate are added to the mixture and stirred for another 10-20 min. The mixture is then transferred to a high-pressure reaction vessel and reacted at 140-150℃ for 12-15 h. After the reaction is completed, the mixture is post-processed to obtain the nickel-cobalt organometallic framework.

5. The boron-doped high-capacity solid-state battery anode material according to claim 4, characterized in that, The ratio of the amounts of pyromellitic acid, anhydrous ethanol, cobalt nitrate hexahydrate, and nickel chloride hexahydrate is 0.6g:70-80mL:0.6g:0.24-0.26g.

6. The boron-doped high-capacity solid-state battery anode material according to claim 1, characterized in that, The polymeric lithium-conducting composite was prepared by the following steps: A1. Under an argon atmosphere, silicon powder, boric acid and boron trioxide are mixed and ball-milled at a speed of 200-400 r / min for 40-60 min. The mixture is then transferred to a tube furnace and heated to 900-1100℃ at a heating rate of 3-5℃ / min. After holding at this temperature for 6-8 h, the mixture is cooled to room temperature with the furnace to obtain boron-doped silicon material. A2. Under an argon atmosphere, boron-doped silicon material is added to a reactor containing toluene and ultrasonically dispersed for 20-30 minutes. Then, polyethylene oxide and lithium tetrafluoroborate are added, the temperature is raised to 50-60℃, and the mixture is stirred at 300-500 r / min for 4-5 hours. After stirring, the mixture is transferred to a vacuum drying oven and dried at 80-90℃ for 8-10 hours. The mixture is then passed through a 200-mesh sieve to obtain a polymer lithium-conducting composite.

7. The boron-doped high-capacity solid-state battery anode material according to claim 6, characterized in that, In step A1, the ratio of silicon powder, boric acid, and boron trioxide is 100g:3-4g:1-2g; in step A2, the ratio of boron-doped silicon material, toluene, and lithium tetrafluoroborate is 100g:400-500mL:8-10g:3-5g.

8. A method for preparing a boron-doped high-capacity solid-state battery anode material according to any one of claims 1-7, characterized in that, The preparation method of the boron-doped high-capacity solid-state battery anode material is as follows: S1. Add the polymer lithium-conducting composite, solid composite electrolyte and conductive carbon black to a mixer and premix for 5-10 min. Then add the styrene-butadiene rubber aqueous solution and stir at 20-30℃ for 20-30 min to obtain the aqueous negative electrode slurry. S2. The aqueous negative electrode slurry is uniformly coated on the surface of copper foil with a coating thickness of 20-30μm. After pre-drying at room temperature for 40-60min, it is transferred to a vacuum drying oven and dried at 60℃ for 2h, and then heated to 80℃ for 6-8h. After drying, the electrode sheet is rolled at 100-120N / mm to obtain boron-doped high-capacity solid-state battery negative electrode material.